Characteristics of particulate matter over the South African industrialized Highveld - Alade, Omotayo Lydia (My University, 2011)
Atmospheric aerosols through their role in heterogeneous chemistry significantly influence the earth’s radiation balance and the radiative budget of the Earth’s atmosphere. The aim of this study is to investigate the characteristics of particulate matter over the industrialised Highveld of South Africa. Elandsfontein, a supersite surrounded by coal mines, coal-fired power stations and a petrochemical plant, is situated on the industrialized Highveld. It provides the monitoring station for the study because it is representative of general conditions of high emissions on the industrialised Highveld region. Continuous measurements of PM10, black carbon, nitrates, sulphur dioxide, particulate sulphate, light scattering properties of aerosol by nephelometer, and meteorological parameters were collected at Eskom’s Elandsfontein air quality monitoring site from January to December 2005. The temporal behaviors of the atmospheric aerosols are investigated on diurnal and seasonal time scales. Effects of meteorological parameters such as temperature, humidity, wind direction, and wind speed on the concentration and properties of the aerosols are determined. Also identified is the fraction of PM10 on the Highveld composed of sulphates, nitrates and black carbon. The causes of particularly high particulate concentrations are discussed. The sources of aerosols are identified and the seasonal effects on the concentration of aerosols are investigated using pollution roses and wind roses. Average concentrations of atmospheric aerosols on the industrialized Highveld are highest during late evenings and at night (18:00-22:00) and lowest during the afternoon (12:00-17:00). Maximum concentrations of aerosols in the early morning and at night indicate the trapping effects of stable atmospheric conditions and surface inversions, suggesting that most particulate matter is derived from sources at the surface or at least from sources below the subsidence inversion layer. Higher humidity in the morning may also enhance particulate matter mass concentration. Concentrations are at a minimum during the day due to atmospheric instability and mixing. Concentrations of nitrate are higher at night especially during winter and are predominantly affected by the same stability phenomenon. Higher concentrations of nitrate during winter nights may be a result of fossil fuel combustion at low level e.g. use of coal for space heating and cooking in townships. During the day NO2 is slowly converted to NO3 by reaction with O3. At night however, the principal reaction of NO3 is with NO2 to set up equilibrium with N2O5. The subsequent heterogeneous dissolution of HNO3 and N2O5 into water droplets gives rise to aerosol nitrate. The night time chemistry of NO3 differs from the daytime behaviour in that it provides a route for conversion of NOx to HNO3 which could be as high as 50% of the daytime route. Sulphate aerosol and sulphur dioxide concentrations peak during the day and are lower at night. Higher concentrations during the day are related to the influence of tall stack emissions from where the sulphur dioxide is derived. Particulate sulphate concentrations are higher in well aged air masses and are controlled by the local meteorology as well as the recirculation pattern of atmospheric aerosol over southern Africa. Particulate concentrations are highest in association with north-westerly winds and lowest in association with easterly winds, since major industries and power plants are located north and south of Elandsfontein. Particulate sulphates sources include oxidation of sulphur dioxide from coal combustion in coal-fired power plants and other industries, and long range air mass transport of sulphate aerosols. The contribution of black carbon and sulphate to PM10 mass is highest in spring while the nitrate contribution to PM10 mass is highest in winter. Some episodes of high particulate matter concentration appear to be related to industrial emissions and fossil fuel combustion. Other episodes are not related to industrial emissions but are mainly due to suspended dust.